Effects of Baduanjin exercise on cognitive frailty, oxidative stress, and chronic inflammation in older adults with cognitive frailty: a randomized controlled trial - Ye, Yu; Wan, Mingyue; Lin, Huiying; Xia, Rui; He, Jianquan; Qiu, Pingting; Zheng, Guohua (Frontiers in Public Health, 2024)
Background Oxidative stress and chronic inflammation play an important role in the pathogenesis process of cognitive frailty (CF). Regular Baduanjin exercise could improve cognitive frailty in older adults, but it is unclear whether the effect of Baduanjin exercise on improving CF is mediated by modulating circulating oxidative stress and inflammatory process. Method A total of 102 community-dwelling older adults with CF were recruited and randomly allocated into a 24-week Baduanjin exercise training group or no specific exercise intervention control group at an equal rate. Cognitive function and physical frailty index were assessed using the Montreal Cognitive Assessment (MoCA) and the Edmonton Frail Scale (EFS), as well as the oxidative stress and inflammatory cytokines were measured at baseline and after intervention. Result After 24 weeks of intervention, the increased MoCA score (2.51 ± 0.32 points, p < 0.001) and the decreased EFS scores (1.94 ± 0.20 points, p = 0.012) in the Baduanjin group were significantly higher than those in the control group. Serum antioxidant SOD levels were increased by 10.03 ± 4.73 U/mL (p < 0.001), and the prooxidative MDA and 8-iso-PGF2α levels were decreased by −1.08 ± 0.80 nmol/mL (p = 0.030) and −86.61 ± 15.03 ng/L (p < 0.001) in the Baduanjin training group; while inflammatory cytokines IFN-γ, IL-2 and IL-4 levels were increased (1.08 ± 0.33 pg./mL, p = 0.034, 2.74 ± 0.75 pg./mL, p = 0.04 and 1.48 ± 0.35 pg./mL, p = 0.042). In addition, a mediation effect that Baduanjin training improved cognitive ability mediated by an increase of circulating IFN-γ and IL-2 levels were observed in this study. Conclusion Regular Baduanjin exercise training could improve the cognitive frailty of the community-dwelling older adults with CF, and modulate oxidative stress and inflammatory processes by reducing circulating pro-oxidative MDA and 8-iso-PGF2α levels and increasing anti-oxidative SOD levels, as well as impacting inflammatory cytokines IFN-γ, IL-2, and IL-4 levels. Nevertheless, the mechanism of Baduanjin exercise mediating oxidative stress and inflammatory processes should be cautious to be explained. Clinical trial registration http://www.chictr.org.cn/index.aspx, ChiCTR1800020341.